2016
DOI: 10.1177/1555412015576613
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Theoretical Framework Based on Motor Play to Categorize and Analyze Active Video Games

Abstract: Active video games (AVG) take the form of motor play (MP) and resemble active practices. In this article, both types of games (AVG and MP) were analyzed, in an effort to find categorical structural criteria shared by both. The main objective of this research is to analyze and propose valid and viable categorical shared criteria to guide the enhancement of AVG analysis. To this end, a comparative analysis that encompasses a description of shared elements, analysis of the ludic structures, description of the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…The present study identified a knowledge gap in research investigated how gender and cultural orientation, alongside their interplay (within multicultural societies), may influence the relationship between depression and DG (Arsenault, 2009;Griffiths et al, 2016;González & Adelantado, 2016;Stavropoulos et al, 2019a). Accordingly, hierarchical linear regression, moderation, and moderated moderation analyses were employed on a normative online sample of gamers coming from multicultural societies to examine these associations (Stavropoulos et al, 2016;Hayes, 2017).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The present study identified a knowledge gap in research investigated how gender and cultural orientation, alongside their interplay (within multicultural societies), may influence the relationship between depression and DG (Arsenault, 2009;Griffiths et al, 2016;González & Adelantado, 2016;Stavropoulos et al, 2019a). Accordingly, hierarchical linear regression, moderation, and moderated moderation analyses were employed on a normative online sample of gamers coming from multicultural societies to examine these associations (Stavropoulos et al, 2016;Hayes, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…Despite the established depression-DG association, there is a dearth of evidence assessing its potential cultural variations. This is imperative in the light of research consistently supporting that symptoms of depression and DG can be moderated by culture (and culturally dictated drives such as those for competitiveness and hierarchy; Arsenault, 2009;González & Adelantado, 2016). Research by Stavropoulos and colleagues (2019) has underscored the importance of such findings in developing culturally responsive interventions for multicultural countries (i.e., Australia and the USA).…”
Section: Depression and Disordered Gamingmentioning
confidence: 99%
“…Other game elements that should be considered in the design of educative videogames in general and for active videogames in particular are collaboration and social aspects [29]. A set of theoretical elements for the design of educational videogames were proposed [30] and for monitoring and evaluating educational videogames [31].…”
Section: Studies About Games and Gamification For Pementioning
confidence: 99%
“…A framework based on the fundamentals of motor play to guide the design and evaluation of active videogames have been developed [29]. Other study, analyzed the effectiveness of commercial active platform (Nintendo Wii) and an active platform designed following principles of educational, collaborative and active videogames [32].…”
Section: Studies About Games and Gamification For Pementioning
confidence: 99%
“…Exergames are digital motor games that aim to stimulate players' motor skills, which are popular on the global market and have been paid increasing attention by educational research [1,2]. As a game type, exergames can be applied to Physical Education (PE), and can simultaneously provide the benefits of motor games [3] and video games [4]. Gamification refers to the use of game-based elements in nongame contexts for motivating actions [5,6].…”
Section: Introductionmentioning
confidence: 99%